Peningkatan Kompetensi Guru Menerapkan Model Pembelajaran Kooperatif Melalui Workshop di SDN 12/X Pemusiran Pada Semester Genap Tahun Ajaran 2021/2022 - Lilis Suryani (Departement of Mathematics Education, 2023)
This study aims to obtain information and discuss increasing teacher competence in applying the cooperative learning model through workshops at SDN 12/X Pemusiran in the even semester of the 2021/2022 academic year. This type of research is school action research. This research was conducted at SDN 12/X Pemusiran in the even semester of the 2021/2022 academic year. The research subjects were all teachers at SDN 12/X Pemusiran, totaling 5 people. Data was collected through observation sheets, field notes, and documentation. Data analysis techniques use percentages and data reduction. Implementation of workshops that focus on increasing teacher competence in applying cooperative learning models, has increased. Based on the results of the research, it can be concluded that through workshops it can increase teacher competence in implementing cooperative learning at SDN 12/X Pemusiran in the even semester of the 2021/2022 academic year.